Lanthanide(III) complexes of a mono(methylphosphonate) analogue of H4dota: the influence of protonation of the phosphonate moiety on the TSAP/SAP isomer ratio and the water exchange rate - Rudovský, Jakub; Cígler, Petr; Kotek, Jan; Hermann, Petr; Vojtísek, Pavel; Lukes, Ivan; Peters, Joop A; Vander Elst, Luce; Muller, Robert N (Chemistry (Weinheim an der Bergstrasse, Germany), 2005)
A monophosphonate analogue of H4dota, 1,4,7,10-tetraazacyclododecane-4,7,10-tris(carboxymethyl)-1-methylphosphonic acid (H5do3aP), and its complexes with lanthanides were synthesized. Multinuclear NMR studies reveal that, in aqueous solution, lanthanide(III) complexes of the ligand exhibit structures analogous to those of H4dota complexes. Thus, the central ion is nine-coordinate, surrounded by four nitrogen atoms, three acetate and one phosphonate oxygen atoms, and one water molecule in an apical position. For complexes of H5do3aP with Ln(III) ions in the middle of the series, the abundance of the desired twisted square-antiprismatic (TSAP) isomer is higher than for the corresponding H4dota complexes. The TSAP/square-antiprismatic (SAP) isomer ratio is highly sensitive to protonation of the phosphonate group: a higher abundance of the TSAP isomer was found in acidic solutions. The microscopic protonation constants of the TSAP isomers are higher than those of the SAP isomers. The presence of one water molecule in the first coordination sphere of the complexes in the pH region studied (pH 2.5-7.0) is confirmed by 17O NMR spectroscopy. The results of a simultaneous fit of variable-temperature 17O NMR relaxation data and 1H NMRD profiles show that the residence time of water (tauM) in the Gd(III) complex is much smaller than for [Gd(dota)(H2O)]-. The exchange rate appears to be dependent on the pH of the solution. The values of tauM are 37, 40, and 14 ns at pH 2.5, 4.7, and 7.0, respectively. These observations can be explained by an extensive second-sphere hydrogen-bonding network that varies with the state of protonation of the phosphonate moiety. Upon protonation of the complex, the second-sphere hydration probably becomes more ordered, which may result in a decrease in penetrability and an increase in tauM. The relaxivity of the Gd(III) complex is almost independent of the pH and is equal to 4.7 s(-1) mM(-1) (20 MHz, pH 7 and 37 degrees C). The solid-state structure was determined for the Nd(III) complex. It crystallizes as the TSAP isomer and the unit cell contains two independent molecules of the complex with different Nd-O(water) bond lengths of 2.499 and 2.591 A.